KONSTRUKSI KELEMBAGAAN KESATUAN PENGELOLAAN HUTAN KONSERVASI ALAS PURWO - , Tri Atmojo, S.Hut, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PP 6/2007 mandates the National Park transformation into Conservation Forest Management Unit (CFMU), including Alas Purwo National Park (APNP).This study is intended filling the institutional transformation because CFMU still using institutional construction of APNP . This research aimed to : (1) provide data and explanation of the current state of institution-building variables of CFMU and stakeholder in APNP, (2) obtain data and explanation about influence of the individual characteristic, transformational leadership, and perception of design organization with attitude of good forestry governance (GFG), (3) obtain the data and an explanation, firstly stakeholder management in APNP, secondly stakeholder relations priorities, thirdly priorities of the principles of GFG, (4) make the construction of institutional design and implementation of regulatory requirements Alas Purwo CFMU. Using case study, this study was conducted between November 2011 and May 2012. We perform data analysis with univariate, multivariate, Analitycal Hierarkhi Process and normative. The research result show that variables of design organization of APNP, GFG attitude, transformational leadership, individual characteristics and funding do not reach the best categories and need improvement as a prerequisite to become innovative CFMU. CFMU institutions are designed organically to replace the mechanistic bureaucracy. Individual characteristics influence the attitude of GFG as CFMU doctrine and become a major element of institutional transformation. Individual characteristics will be driven by transformative leadership that able to perform empowerment of all personnel. Funding is going to use government funds and green partnership to manifest the independence of the institution. CFMU construction is a multi partnership organizations. PHKA and society become a major force to guard the process of governance. Law certainty and ecological norms animates the process of governance and executed synergistically with socioeconomic norms, transparency, participation and accountability as an operational guide of CFMU. The main indicators of institutional success is Alas Purwo CFMU become patron of stakeholders and is able to be model of CFMU in Indonesia. For running the CFMU, we should revise UU No.5/1990, UU No.41/1999, PP 28/2011 and should make the Permenhut of CFMU which consist of organization design, HRD, NSPK, funding, partnerships and indicators of institutional succes.